British Colonial Marine Transport Services in the Niger-Benue Confluence Area of Nigeria, 1914–1918 - Shuaibu, Mohammed Lawal (ABUAD Journal of Social and Management Sciences, 2022)
This paper focuses on the British marine transport services in the Niger-Benue confluence area of Nigeria during the First World War. It posits that the flow of the Benue River through the Northern Nigeria/Cameroon border was a major way through which the British war resources were conveyed from the Niger-Benue confluence area to the battlefronts against the German Cameroon. The paper claims that the British authorities used lies as strategy by painting the Germans as land grabbers to get the locals’ commitment and support during the war at the expense of marine transport services. It reveals that the colonial authorities’ deployment of marine personnel and facilities in the prosecution of the war almost paralysed marine transport services in the area and beyond. The Marine Department (MD), the colonial authority that provided marine services on the waterways, lost 40 British marine officers, 4000 Nigerian personnel and had 12 of its vessels destroyed in the war. The deployment, as discovered, made the MD to neglect its primary responsibilities of maintaining and providing marine transport services in the Niger-Benue confluence area in particular, and Nigeria in general. The development affected nearly every other part of colonial Nigeria economically as the utilisation of Niger-Benue Rivers (which formed the major navigable trading routes) for the war created shortages of imports and scarcity of shipping resources. A wide range of sources from primary to textual analyses in extant literature are used to explain how marine transport in the confluence area fared during the First World War.